1975
DOI: 10.1111/j.1476-5381.1975.tb07323.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sympathomimetic Amines on the Ventricular Fibrillation Threshold in the Rabbit Isolated Heart

Abstract: 1The ventricular fibrillation threshold (VFT) was measured in the isolated heart of the rabbit perfused via the aorta with McEwen's solution at 370C by applying a single 10 ms pulse of current during the vulnerable period of late systole. The arrhythmia induced was either fibrillation or a rapid tachycardia. 2 The catecholamines adrenaline, noradrenaline and isoprenaline, but not dopamine, when infused at rates which produced similar moderate effects on cardiac rate and force, significantly lowered the VFT; it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Epinephrine enhances automaticity, lowers fibrillation thresholds [17,18,27,29,30] and increases extrasystoles [28,31]. The effects on the action potential vary, but epinephrine alters calcium handling and increases the likelihood of delayed after-depolarizations [32][33][34][35].…”
Section: Epinephrine and Arrhythmic Riskmentioning
confidence: 99%
“…Epinephrine enhances automaticity, lowers fibrillation thresholds [17,18,27,29,30] and increases extrasystoles [28,31]. The effects on the action potential vary, but epinephrine alters calcium handling and increases the likelihood of delayed after-depolarizations [32][33][34][35].…”
Section: Epinephrine and Arrhythmic Riskmentioning
confidence: 99%
“…The effect of the released catecholamines in the whole animal, however, are complex as have shown that infused adrenaline first lowers and then raises the VFT in the dog. Although anoxia causes the release of noradrenaline in the rabbit isolated perfused heart (Wollenberger & Shahab, 1965) and noradrenaline lowers the VFT (Murnaghan, 1975), the released noradrenaline cannot be responsible for the fall in the VFT induced by anoxia because the effect is not prevented by blockade of the,-adrenoceptors by propranolol or pindolol or by previous depletion of noradrenaline in the heart by reserpine.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence that the release of noradrenaline is not responsible for the fall in the VFT during anoxia is the fact that the fall was not prevented by previous treatment with reserpine (VFT change ratios of 0.44, 0.50 and 0.29 in three trials in one heart). The 1-blockers alone in 15 trials did not significantly alter the VFT change ratio (0.95 ± 0.11) but have been shown to block the lowering effect of noradrenaline on the VFT (Murnaghan, 1975).…”
Section: Ventricular Fibrillation Thresholdmentioning
confidence: 99%
See 2 more Smart Citations